Russia as Mediator in US-Iran Crisis? - Cheang, Chris (2020)
The killing of Iranian military commander,Qassem Soleimani in a US drone strike on Iraqi soil last week presents Russia with a godsent: it will not only increase its prestige and influence in the Middle East but more importantly, further weaken Western attempts to isolate it.